Notas sobre o Trabalho Social cubano - Silva, José Fernando Siqueira Da; Carmo, Onilda Alves Do (Cortez Editora Ltda, 2015)
This paper analyses social work in Cuba, its challenges and perspectives. It also emphasizes ways and possibilities to reaffirm the present importance of critical debate among Cuban social worker and the necessary dialogue with Marx's social theory.

O presente texto analisa o Trabalho Social em Cuba, seus desafios e perspectivas. Destaca, ainda, caminhos e possibilidades para reafirmar a atualidade do debate crítico entre os trabalhadores sociais cubanos e sua necessária interlocução com a teoria social de Marx.
Notes on Cuban social work
Keywords: Social transition; Marx's social theory; Social Work.; Transição socialista; Teoria social de Marx; Trabalho Social.